2010
DOI: 10.1155/2010/252609
|View full text |Cite
|
Sign up to set email alerts
|

A Robotic Guide for Blind People. Part 1. A Multi-National Survey of the Attitudes, Requirements and Preferences of Potential End-Users

Abstract: This paper reports the results of a multi-national survey in several different countries on the attitudes, requirements and preferences of blind and visually impaired people for a robotic guide. The survey is introduced by a brief overview of existing work on robotic travel aids and other mobile robotic devices. The questionnaire comprises three sections on personal information about respondents, existing use of mobility and navigation devices and the functions and other features of a robotic guide. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In the past, little attention has been paid to the aesthetics of many types of assistive devices [48]. However, research shows that end-users consider device appearance to be very important and want assistive devices to be elegant and attractive [58,59]. End-users may also be expected to be grateful that devices are available regardless of any associated stigma or negative image [48].…”
Section: Stigma Disability and Assistive Devicesmentioning
confidence: 99%
“…In the past, little attention has been paid to the aesthetics of many types of assistive devices [48]. However, research shows that end-users consider device appearance to be very important and want assistive devices to be elegant and attractive [58,59]. End-users may also be expected to be grateful that devices are available regardless of any associated stigma or negative image [48].…”
Section: Stigma Disability and Assistive Devicesmentioning
confidence: 99%
“…Several studies (e.g. Arras and Cerqui 2005, Hersh and Johnson 2010, Oestreicher 2007and Wu et al 2012 have found that potential users preferred a robot looking like a machine to one with a humanoid appearance. On the other hand, other studies indicate that people prefer software agents with human faces (Kiesler and Sproull 1997 ;Koda and Maes 1996 ;Takeuchi and Naito 1995 ), robots with a more human appearance (Hinds et al 2004 ) and robots to communicate in a humanlike way (Dautenhahn et al 2005 ).…”
Section: Legged Robotsmentioning
confidence: 99%
“…Alongside visual manipulation approaches, haptic feedback can be used to induce changes in walking direction. One example, is the use of robotic guide dogs, who can help to guide the visually impaired safely along paths (Chuang et al, 2018), which may be implemented so that the user holds onto a cane/handle (Chuang et al, 2018), and when the robot turns the user receives haptic feedback based on the mass of the robot indicating movement (Hersh and Johnson, 2010). Another example is galvanic vestibular stimulation in which the placement of electrodes behind an individual's ear, can induce postural adjustments through the use of electrical currents (Maeda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%